2008
DOI: 10.1002/smll.200701316
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles as a Delivery System of Gadolinium for Effective Human Stem Cell Tracking

Abstract: The progress of using gadolinium (Gd)-based nanoparticles in cellular tracking lags behind that of superparamagnetic iron oxide (SPIO) nanoparticles in magnetic resonance imaging (MRI). Here, dual functional Gd-fluorescein isothiocyanate mesoporous silica nanoparticles (Gd-Dye@MSN) that possess green fluorescence and paramagnetism are developed in order to evaluate their potential as effective T1-enhancing trackers for human mesenchymal stem cells (hMSCs). hMSCs are labeled efficiently with Gd-Dye@MSN via endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(137 citation statements)
references
References 31 publications
5
130
1
1
Order By: Relevance
“…42 This work sought to answer two questions: (1) Can SiGNRloaded MSCs still differentiate? 43 and (2) Does the presence of SiGNRs induce any unintended differentiation? We were especially concerned that the SiGNRs might unintentionally transform MSCs into osteogenic cells as silicon-based structures have previously been show to induce such differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 This work sought to answer two questions: (1) Can SiGNRloaded MSCs still differentiate? 43 and (2) Does the presence of SiGNRs induce any unintended differentiation? We were especially concerned that the SiGNRs might unintentionally transform MSCs into osteogenic cells as silicon-based structures have previously been show to induce such differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The next generation of this contrast agent may have a larger aspect ratio to induce longer red-shifted resonances. 56 Finally, we will dope Gd 3+ into the silica shell of the SiGNRs for T1 magnetic resonance imaging 43 to complement the PA mode for long-term monitoring of implanted MSCs with greater depth of penetration. Bmode imaging for visualization of the delivery catheter and the in vivo environment is complemented nicely by PA-mode that specifically enhances MSC signal.…”
Section: Discussionmentioning
confidence: 99%
“…8 The nanoparticles could remain in the cells for several days; for example, the cells prelabeled with nanoparticles for 7 days could still be detected by MRI. 21 Stem cells are functionally defined by their capacity for self-renewal and differentiation into multiple cell types. MSCs can differentiate into various types of cells under various conditions, such as adipocytes, osteocytes, chondrocytes, and neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The mesoporous structure can hold paramagnetic gadolinium (Gd) ions, allowing easy water access to Gd ions and a high degree of interaction between Gd ions and water protons, which contribute to increasing MR signals. [16][17][18][19][20] Hsiao et al 21 first reported on an efficient stem cell-tracking media made by Gd-loaded mesoporous silica nanoparticles that did not affect cell viability or differentiation; this laid the foundation for future visual stem cell therapies using T 1 -weighted MRI with a Gd-based positive contrast agent instead of superparamagnetic iron oxide (SPIO). Additionally, monitoring the fate of transplanted cells in vivo is an increasingly indispensable part of assessing the nanoprobe as a cellular tracer; in particular, the combination of MR images with histological analysis provides for a more thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Equally, mesoporous silica nanoparticles, either functionalized with different amounts of positively charged functional groups or with gadolinium, did not influence MSC differentiation, as confirmed by qualitative analyses after short-term exposure. 104,105 In addition to the effects on the differentiation potential, further MSC functions can be modulated by nanoparticles. Ferucarbotran particles with superparamagnetic properties were efficiently taken up by MSCs.…”
mentioning
confidence: 99%